2003
DOI: 10.2307/1568802
|View full text |Cite
|
Sign up to set email alerts
|

'Laudianism' in Scotland? St Giles' Cathedral, Edinburgh, 1633-39: A Reappraisal

Abstract: The liturgical and sacramental policies of the 1630s had a direct impact upon the architecture and furnishings of English cathedrals and parish churches. Archbishop Laud, in particular, was associated with the restoration of altars, which meant the rearrangement of church interiors and the removal of pews so that communion tables could be erected at the east end of the church. There was also a concerted effort to take down seating galleries and, externally, to remove buildings and shops which encroached upon t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In 1637 he ordered that ' all things concerning the cathedral ' of Edinburgh were to be directed by three Anglophile Scots : Bishop David Lindsay of Edinburgh, who had defended the ceremonies of the Church of England in print, Dean James Hannay of Edinburgh, who had recently been sent to Durham to obtain ' ane plott of the queir ' as a blueprint for Edinburgh, and Archbishop John Spottiswoode of St Andrews, who boasted that he had 'adorn'd ' his private chapel 'after the decent English form '. 17 Shortly before the king's command, a merchant burgess of Edinburgh had noted that work had begun to convert the new cathedral with an altar and choristers and organs 'and sic uther thingis as is necessarie for ye qur of ane Cathedrall kirke ' which were, he had already bewailed, ' acording to ye order … & ye liturgie of ingland '. 18 Morrill has suggested that James VI and I and Charles I aimed at 'congruity ' between the churches of their kingdoms, 19 but when it came to the cathedrals of their three capitals, something more akin to unity of purpose and status seems to have been the goal.…”
mentioning
confidence: 99%
“…In 1637 he ordered that ' all things concerning the cathedral ' of Edinburgh were to be directed by three Anglophile Scots : Bishop David Lindsay of Edinburgh, who had defended the ceremonies of the Church of England in print, Dean James Hannay of Edinburgh, who had recently been sent to Durham to obtain ' ane plott of the queir ' as a blueprint for Edinburgh, and Archbishop John Spottiswoode of St Andrews, who boasted that he had 'adorn'd ' his private chapel 'after the decent English form '. 17 Shortly before the king's command, a merchant burgess of Edinburgh had noted that work had begun to convert the new cathedral with an altar and choristers and organs 'and sic uther thingis as is necessarie for ye qur of ane Cathedrall kirke ' which were, he had already bewailed, ' acording to ye order … & ye liturgie of ingland '. 18 Morrill has suggested that James VI and I and Charles I aimed at 'congruity ' between the churches of their kingdoms, 19 but when it came to the cathedrals of their three capitals, something more akin to unity of purpose and status seems to have been the goal.…”
mentioning
confidence: 99%